PENGARUH STRES KERJA DAN BUDAYA KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS PENDIDIKAN KABUPATEN TORAJA UTARA - Melvipatricia Ampu Lembang; Jens Batara Marewa; Marinus Ronal (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
This study aims to examine the effect of work stress and work culture on employee performance at the Education Office of North Toraja Regency. A quantitative research approach was employed using questionnaires and documentation for data collection. The study involved 46 employees, all of whom were selected as respondents through a census sampling technique. Data were analyzed using IBM SPSS with multiple linear regression, t-test, and F-test. The results revealed that work stress had no significant effect on employee performance, as indicated by a calculated t-value of -1.690, which was lower than the critical t-value of 2.016, with a significance level of 0.098 (>0.05). In contrast, work culture had a positive and significant effect on employee performance, with a calculated t-value of 5.525, exceeding the critical value of 2.016 and a significance level of 0.000 (<0.05). Simultaneously, work stress and work culture significantly influenced employee performance, as evidenced by an F-value of 19.563, which was greater than the F-table value of 3.21, with a significance level of 0.000 (<0.05). These findings indicate that work culture is the dominant factor in improving employee performance.